Discursos de professores dos anos iniciais do ensino fundamental sobre as tecnologias no ensino de matemática - Silva, Valéria Gomes da (2013)
The present study makes a reflection and analysis of the speeches of eight teachers that work in the early years of elementary school in two public schools at the city hall of Uberlândia, on technologies in the teaching and learning of Mathematics. The proposed goals were to identify the design of teachers in the early years of elementary school about what they understand by technology. Know the challenges/barriers encountered by teachers in relation to the use of technology in their educational practices in teaching mathematics. Discover whether teachers consider technology as an effective tool in the teaching and learning of mathematics in the early years of elementary school. Moreover to reflect about the use of technology in the educational practices of teachers working in the early years of elementary school. The methodological way adopted to address the problem of this study was a qualitative study. Two data collection instruments were used: the questionnaire and the interview recorded. The questionnaires were applied in order to characterize the subjects and interviews were used in order to understand the discourse of teachers regarding technology in teaching and learning. To select the teachers who were interviewed we have established two criteria. In the first criterion of the interview, it was required that the teachers had completed their undergraduate degree in the last five years, from 2006. In the second criterion of the interview, the selected teachers had little work experience in the profession. To analyze the interviews, we have used the content analysis method. Because this technique allows us to understand and interpret the speech of the individual participating on this interview. The results of this study show that teachers have the idea that technology is strictly a machine. The technological device has also demonstrated a lack of knowledge of them to integrate technology in their educational practices. For teachers, technology is a mean in itself that cause changes in the processes of teaching and learning. Besides, the results also demonstrate that the teachers resist to the use of technology in their educational practices. Which is a consequence of the difficulties encountered by them to articulate their pedagogical proposals with the technologies.